Influência do uso precose de mídias digitais no desenvolvimento de crianças atípicas de 3 a 4 anos: estudo situado e conscientização dos responsáveis - Pitanga, Isleide Costa Freire Vasconcellos (My University, 2026)
This study investigated the influence of early use of digital media on the development of atypical children aged 3 to 4 years, considering the perspective of inclusive education and caregiver awareness. In this way, the following research question is formulated: how are caregivers dealing with the use of digital technologies in the daily lives of children served by Early Childhood Intervention? The aim was to analyze caregivers’ perceptions of the impacts of screen use on children’s overall development, identify whether they promote playful interactions in daily life or replace these experiences with technology, understand developmental milestones of atypical children, and propose an educational resource to encourage interactive play. The research involved 27 caregivers, and their children enrolled in the Early Education Program at the Special Education Center 02 in Brasília, including children with intellectual disabilities, multiple disabilities, and autism spectrum disorder. A qualitative, exploratory, and descriptive approach was adopted, using a structured questionnaire adapted from Azevedo’s (2020) dissertation, the Operationalized Portage Inventory (IPO), and observation records. The study followed five stages: literature review, institutional authorization, submission to Plataforma Brazil, data collection, and data analysis. Results showed that although 16 caregivers initially denied it, all children had some contact with digital media, often at an early age and contrary to expert recommendations. Caregivers recognized the importance of play but frequently used screens for entertainment, distraction, or behavior management, particularly in situations of family overload. A gap in professional guidance regarding healthy media use was observed. IPO assessments indicated that 15 of the 27 children demonstrated development below the expected average across all evaluated areas (socialization, language, self-care, cognition, and psychomotor skills), with language delays being the most prominent (16 cases in comprehension and 17 in expression). The study suggests that unmediated screen use tends to replace interactive experiences and play, which are essential for higher psychological functions, according to Vygotsky. As a final proposal, an educational resource was developed, comprising playful workshops using sustainable materials and an informational booklet, aimed at guiding families and reinforcing practices that support child development. The study highlights the urgent need for caregiver awareness and intersectoral public policies to ensure conscious use of technology in early childhood.
Keywords: criança; mídias digitais; desenvolvimento global infantil; educação precoce; educação inclusiva; HUMANITIES and RELIGION::Languages and linguistics::Linguistic subjects::Children's language; digital media; child global development; early education; inclusive education